The effectiveness of Mobile Learning in UAE Universities: A systematic review of Motivation, Self-efficacy, Usability and Usefulness - Hafidha Bettayeb, Dr. Muhammad Turki Alshurideh, Dr. Barween Al Kurdi (International Journal of Control and Automation, 2020)
Information technology (IT) represents a fundamental force of change in the contemporary era. The ease of use and low cost of mobile technologies make IT accessible for students of all education levels. Mobile learning effectiveness (M-Learning) represents a significant study area in the education sector. This paper presents a systematic review of the existing literature on M-Learning within the university context with the underlying intention of investigating the factors that contribute to effective M-Learning. The findings highlight the need to focus on improving the self-efficacy, ease of use, and effectiveness of mobile learning.        In total, 495 articles that were of potential relevance to the analysis that were written between 2010 and 2020 and published on EBSCO, Google Scholar, ProQuest One Academic, Science Direct, or Scopus databases were screened. After scanning and filtering according to the inclusion and exclusion criteria, 30 articles were included in the literature review. The data and independent and dependent variables examined within the articles were reviewed to identify the factors that contribute to effective M-Learning.